Public Service Delivery in Cambodia: A Review of the One Window Service Office (OWSO) Implementation - Thay, Kosal; Serey, Mardy (JPS: Journal of Publicness Studies, 2026)
Public service delivery in developing countries is a fundamental component of state-building, governance reform, and poverty reduction. Cambodia's shift from a centralized post-conflict administration to decentralized governance has been characterised by considerable organisational reform. Central to these endeavours is the One Window Service Office (OWSO) programme, a local government provision system which adopts a single-agency approach to increase transparency, accountability and effectiveness in local public administration services. The article offers an account of the OWSO model in Cambodia according to IMRAD (Introduction, Methods, Results, Discussion). This paper analyzes OWSO's performance on service quality and citizen satisfaction, based on a systematic review of research findings in academic literature, governmental reports, and international development assessments. It also argues that while the OWSO has successfully streamlined administrative procedures, reduced informal payments, and generated substantial state revenue, the ongoing effectiveness of OWSO is hampered by short staffing levels, poor digital infrastructure and enduring rural and urban divides. Comparison of regional models in Southeast Asia like Indonesia at PTSP and ARTA in the Philippines shows the importance of strong digital integration and sustained political will. The article concludes with policy recommendations aimed at furthering the public administration reform agenda in Cambodia.